САМОВИХОВАННЯ ЯК ЗАСІБ ПРОФІЛАКТИКИ ДЕВІАНТНОЇ ПОВЕДІНКИ ПІДЛІТКІВ - Янц, Наталія; Підгорна, Надія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття присвячена проблемі профілактики девіантної поведінки підлітків. У ході дослідження висвітлено вікові особливості підлітків та з’ясовано специфіку самовиховання в цьому віці. Доведено, що одним із засобів попередження девіантної поведінки є організація науково обґрунтованої роботи з формування в підлітків здатності до само-виховання. Установлено, що процес самовиховання в підлітковому віці потребує кваліфікованого педагогічного керівництва. Статья посвящена проблеме профилактики девиантного поведения подростков. В ходе исследования освещены возрастные особенности подростков и выяснено специфику самовоспитания в этом возрасте. Доказано, что одним из средств предупреждения девиантного поведения является организация научно обоснованной работы по формированию у подростков способности к самовоспитанию. Установлено, что процесс самовоспитания в подростковом возрасте требует квалифицированного педагогического руководства. The article deals with the problem of prevention of deviant behavior of adolescents. The aim of the article is the disclosure of the nature and characteristics of self-education as a means of prevention of deviant behavior among adolescents. The study highlights the age characteristics of adolescents and found self-education specifics at this age. Proved that one means of preventing deviant behavior is a science-based organization working to build a teen’s ability to self-education. Namely, the self-education activates all types of teenager’s activity and encourages identify meeting efforts in relation to the studies, education and development, helps better to understand itself, estimate the possibilities, overcome bad habits, learn the rules and regulations of life, directing at independent and informed choice of the future life. It’s established, that efficiency of work organization with self-education of teenagers depends on system, structure and qualified teacher leadership.